Effect of nanoprecipitates on the transformation behavior and functional properties of a Ti–50.8 at.% Ni alloy with micron-sized grains. (1st January 2015) - Wang, Xiebin; Kustov, Sergey; Li, Kai; Schryvers, Dominique; Verlinden, Bert; Van Humbeeck, Jan
Abstract: In order to take advantage of both grain refinement and precipitation hardening effects, nanoscaled Ni4 Ti3 precipitates are introduced in a Ti–50.8 at.% Ni alloy with micron-sized grains (average grain size of 1.7 μm). Calorimetry, electrical resistance studies and thermomechanical tests were employed to study the transformation behavior and functional properties in relation to the obtained microstructure. A significant suppression of martensite transformation by the obtained microstructure is observed. The thermomechanical tests show that the advantageous properties of both grain refinement and precipitation hardening are combined in the developed materials, resulting in superior shape memory characteristics and stability of pseudoelasticity. It is concluded that introducing nanoscaled Ni4 Ti3 precipitates into small grains is a new approach to improve the functional properties of NiTi shape memory alloys.